2019
DOI: 10.1186/s12879-019-4185-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of infectious aetiologies of acute undifferentiated febrile illnesses in south and Southeast Asia: a systematic review

Abstract: Background: Acute undifferentiated febrile illness (AUFI) is caused by a multitude of diverse pathogens, with significant morbidity and mortality in the developing world. The objective of this review was to characterise the diversity and relative importance of common infectious aetiologies of AUFI in South and Southeast Asia. Methods: We conducted a comprehensive literature review to identify common aetiologies of AUFI in Asian countries. Four medical and life sciences databases including PubMed, Medline, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 76 publications
3
53
2
Order By: Relevance
“…Rickettsial infections are among the most important causes of non-malarial fever in Southeast Asia (Acestor et al, 2012;Wangdi et al, 2019). Rickettsial bacteria are obligate intracellular Gram-negative coccobacilli that are transmitted to humans through bites of infected fleas, mites, ticks and lice (Trung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Rickettsial infections are among the most important causes of non-malarial fever in Southeast Asia (Acestor et al, 2012;Wangdi et al, 2019). Rickettsial bacteria are obligate intracellular Gram-negative coccobacilli that are transmitted to humans through bites of infected fleas, mites, ticks and lice (Trung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, diagnosis of these RDs is missed, as seen in 66.5% of scrub typhus cases [1] and in 57.9% of Mediterranean spotted fever (MSF) cases [2]. Among acute undifferentiated febrile illness (AUFI/AFI) cases from Asia, 4% of cases were caused by RD overall and among adults 12.5% of AFI cases [3]. Among the pediatric population, AFI due to RD occurred in 0.4 to 7.4% in East Africa, 2 to 17% in South Asia, 0.5 to 20.1% in SE Asia, and 7.5% in Latin America [4].…”
Section: Introductionmentioning
confidence: 99%
“…A change in disease pattern has indeed been documented elsewhere, 27,28 and it has been found that dengue comes with a wider spectrum of symptoms than previously observed. [29][30][31] To overcome the diagnostic challenges mentioned, a solid system must be in place, which gives the clinicians the best possible prerequisites for making the correct diagnosis and, thus, the health authorities a correct picture of the disease burden. This includes a standardized regulatory framework for diagnostics and case reporting, access to the best diagnostic tools, staff with proper qualifications, and a well-functioning leadership and governance.…”
Section: Discussionmentioning
confidence: 99%
“…A change in disease pattern has indeed been documented elsewhere, 27 , 28 and it has been found that dengue comes with a wider spectrum of symptoms than previously observed. 29 31 …”
Section: Discussionmentioning
confidence: 99%